Influence of Forming of System of «Green» Public Procurements on Market Development of Environmentally Friendly Products - Anna Nikolaevna Kazantseva (Управленческое консультирование)
As a result of increase in anthropogenous impact at the environment, growth of number of environmental disasters, there is a task of decrease in negative impact on the surrounding environment more and more sharply. Transition of economy of the state to sustainable development can become one of solutions of this problem. It will demand establishment of balance between economy, ecology and the social sphere. The system of «green» public procurements can become one of the tools promoting greening of economy, including market development of environmentally friendly products. In this article the need of greening of production promoting market development of environmentally friendly products is analyzed. The analysis of development of greening of sectors of economy in the countries of the world is carried out, the conclusion is drawn on the prospects of development of system of “green” public procurements, including the author offered completions in the Federal Law N44 «About contractual system in the sphere of purchases of goods, works, services for ensuring the state and municipal needs».